Effective scale for consumers' environmental concerns: A competing scales study between NEP and ECCB - Freire, Otavio; Quevedo-Silva, Filipe; Frederico, Elias; Vils, Leonardo; Braga Junior, Sergio Silva [UNESP] (Elsevier B.V., 2021)
The purpose of this article is to analyze which scale is more effective in measuring consumer environmental concerns. Specifically, we compared the New Ecological Paradigm (NEP) and Ecologically Conscious Consumer Behavior (ECCB), analyzing which better represents ecological concerns relative to the behavioral intention of the ecologically responsible consumer. An online survey was performed with 736 consumers. Structural equations modeling was performed. Results indicate that ECCB presents greater explicative power and seems to be more adequate than NEP in measuring ecological concerns. When we compare the two scales most frequently used by researchers in the world, we not only find which is the most fitting but also identify the real need to build a more suitable scale to measure the construct. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Environmental concern; Ecological consumer; Competing scales; NEP; ECCB